Relationships of phenology, photosynthesis and respiration in cotton plants selected for high and low starch content in roots - Souza, José Gomes de; Silva, Jorge Bravo vieira da (Pesquisa Agropecuaria Brasileira, 1994)
A comparison between two cultivars obtained by recurrent selection for low and high starch accumulation in the root system, and the parent cultivar, shows under greenhouse conditions that photosynthetic rate was not modified, but decreased with senescence, as well as did respiration. Leaf respiration activity however is higher in the cultivar selected for high starch content than in the cultivar selected for low starch content. The photosynthetic and respiration in leaves of the same sympodium are similar. The selection process increased the size of bolls in the high starch variety both in greenhouse and in the field. Fiber quality was also modified in the high starch variety, with greater length and a decrease in maturity. Under field conditions selecting for high root starch content decreased height but conserved yield. Selection for low starch accumulation decreased yield. It is verified that selecting for high starch content in roots modified the phenology of the cotton plant decreasing the strength of the terminal bud sink, without modifying photosynthetic ability.
Keywords: source-sink; fiber quality; bolls